Assessing the effects of probiotic supplementation, single strain versus mixed strains, on femoral mineral density and osteoblastic gene mRNA expression in rats - Parvaneh, Maria; Jamaluddin, Rosita; Ebrahimi, Mahdi; Karimi, Golgis; Sabran, Mohd Redzwan (Springer, 2024)
Introduction: Osteoporosis is a significant health concern characterized by weak and porous bones, particularly affecting menopausal women aged 50 and above, leading to increased risk of hip fractures and associated morbidity and mortality. Materials and Methods: We conducted a study to assess the efficacy of single-strain versus mixed-strain probiotic supplementation on bone health using an ovariectomy (OVX) rat model of induced bone loss. The probiotics evaluated were Lactobacillus helveticus (L. helveticus), Bifidobacterium longum (B. longum), and a combination of both. Rats were divided into five groups: SHAM (Control negative), OVX (Control positive), OVX +L. helveticus, OVX + B. longum, and OVX + mixed L. helveticus and B. longum. Daily oral administration of probiotics at 10^8-10^9 CFU/mL began two weeks post-surgery and continued for 16 weeks. Results: Both single-strain and mixed-strain probiotic supplementation upregulated expression of osteoblastic genes (BMP- 2, RUNX-2, OSX), increased serum osteocalcin (OC) levels, and improved bone formation parameters. Serum C-terminal telopeptide (CTX) levels and bone resorption parameters were reduced. However, the single-strain supplementation demonstrated superior efficacy compared to the mixed-strain approach. Conclusion: Supplementation with B. longum and L. helveticus significantly reduces bone resorption and improves bone health in OVX rats, with single-strain supplementation showing greater efficacy compared to a mixed-strain combination. These findings highlight the potential of probiotics as a therapeutic intervention for osteoporosis, warranting further investigation in human studies. © The Japanese Society Bone and Mineral Research 2024.